Improvisando a gestão por meio da gestão do improviso : o processo de trabalho dos gestores de um hospital universitário federal - Littike, Denilda (2012)
This research aims to analyze the process of work of the Division managers HUCAM. Specifically to understand the work of managers and the relationship with their health, and identify whether the Manager had some illness that they related to this work. Supported the concept of working process of Karl Marx. It was recognized that the work operates on job object transformations and the worker. In the context of a hospital worker activity shall organise the work of many others. In order to achieve the proposed objectives were held 12 individual interviews with the managers of the Division, between September and October 2011. As research instrument was used a semi-structured roadmap, and the analysis of the testimony was done qualitatively. In this study it was observed the ethical conduct in research. The results showed that the job object managers are organizational issues. To perform their activities, they mainly use their knowledge and the memorandum; planning as a management tool, has rarely been used. The subject of this study do not have a defined working routine. Identified that their agendas are always abarrotas by various conflicts that emerge in the institution. His work has been shaped by the Organization of the work of the HUF. The organisation chart of HUCAM demonstrates a pyramidal administrative structure whose services are separated by areas, and each hierarchical level has its Manager. However, in practice, workers resist submitting to this organizational model. Noise in the communication were identified, and conflicts between the three hierarchical levels and between the various services. Were not identified collective spaces of permanent negotiation between division managers and directors of the HUF. Press for a fragmented management practice and improvised, without political analysis of the decisions taken. It should be noted that collective management is attribution. We apprehend that the arduous task of contributing to keep the HUCAM in operation, which takes contours of a fight against death of own hospital, does emerge in the subject of this study a feeling of frustration and disbelief with projects of change for the better in the management of HUCAM. However, it was realized that exercise the function of Manager in a HUF also constitutes a source of senses of fulfillment and pleasure for the employee-Manager. It is understood that this contributes to they continue in the exercise of this activity, although it stood out in testimony the discourse of demotivation. In the end, it is concluded that the Organization of work and the process of work of the Division managers influence their health, with a view to the symptoms: increased blood pressure, mental fatigue, headache, among others, for they reported as arising from the work in management. Points out the need for more research about the work of managers, and the production plan of the HUF 's.